Ionotropic Receptor-dependent cool cells control the transition of temperature preference in Drosophila larvae. - Jordan J Tyrrell; Jackson T Wilbourne; Alisa A Omelchenko; Jin Yoon; Lina Ni (PLoS Genetics)
Temperature sensation guides animals to avoid temperature extremes and to seek their optimal temperatures. The larval stage of Drosophila development has a dramatic effect on temperature preference. While early-stage Drosophila larvae pursue a warm temperature, late-stage larvae seek a significantly lower temperature. Previous studies suggest that this transition depends on multiple rhodopsins at the late larval stage. Here, we show that early-stage larvae, in which dorsal organ cool cells (DOCCs) are functionally blocked, exhibit similar cool preference to that of wild type late-stage larvae. The molecular thermoreceptors in DOCCs are formed by three members of the Ionotropic Receptor (IR) family, IR21a, IR93a, and IR25a. Early-stage larvae of each Ir mutant pursue a cool temperature, similar to that of wild type late-stage larvae. At the late larval stage, DOCCs express decreased IR proteins and exhibit reduced cool responses. Importantly, late-stage larvae that overexpress IR21a, IR93a, and IR25a in DOCCs exhibit similar warm preference to that of wild type early-stage larvae. These data suggest that IR21a, IR93a, and IR25a in DOCCs navigate early-stage larvae to avoid cool temperatures and the reduction of these IR proteins in DOCCs results in animals remaining in cool regions during the late larval stage. Together with previous studies, we conclude that multiple temperature-sensing systems are regulated for the transition of temperature preference in fruit fly larvae.